Novel method to quantify peptidylarginine deiminase activity shows distinct citrullination patterns in rheumatoid and juvenile idiopathic arthritis - Yu, Karen; Dillemans, Luna; Gouwy, Mieke; Bessa, Helena; Metzemaekers, Mieke; Martens, Erik; Matthys, Patrick; Bossuyt, Xavier; Verschueren, Patrick; Wouters, Carine; De Somer, Lien; Proost, Paul (Frontiers in Immunology, 2023)
Peptidylarginine deiminases (PADs) mediate citrullination, an irreversible posttranslational modification that converts arginine to citrulline residues in proteins. Rheumatoid arthritis (RA) is characterized by unique autoantibodies that recognize citrullinated peptides, which are highly specific for this disease. However, the mechanism preceding the anti-citrulline response remains largely unclear. PAD enzymes are known to fuel the autoimmune response by generating autoreactive epitopes, and sustain local synovial inflammation through neutrophil extracellular trap formation. Therefore, detecting endogenous PAD activity is important to understand the pathogenesis of arthritis. In this study, we improved a fluorescent in vitro assay to enable endogenous enzyme activity characterization in complex samples. This pioneering PAD assay allowed profiling of active citrullination in innate leukocytes and in local and systemic samples of an arthritis cohort. Our results reveal that RA and juvenile idiopathic arthritis (JIA) synovial fluids display similar levels of PAD activity. In contrast, citrullination was limited in joints of patients suffering from gout or Lyme’s disease. Interestingly, in blood, a higher level of extracellular citrullination was only found in anti-CCP-positive RA patients. This finding suggests that enhanced synovial PAD activity drives the loss in tolerance towards citrullinated proteins and that systemic citrullination may indicate the risk for developing citrulline-specific autoimmunity.